If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-18/17=x/17
We move all terms to the left:
-18/17-(x/17)=0
We add all the numbers together, and all the variables
-(+x/17)-18/17=0
We get rid of parentheses
-x/17-18/17=0
We multiply all the terms by the denominator
-x-18=0
We add all the numbers together, and all the variables
-1x-18=0
We move all terms containing x to the left, all other terms to the right
-x=18
x=18/-1
x=-18
| 59=8d-37 | | 8.7y=3.9y+6 | | 50=8d-37 | | 2c+-3=-7 | | 1.4=3y+13.1 | | (3m+4)= | | -24+3(1+4x)=-19 | | 7x^-2=x-4 | | 2w(5w-2)=-5w+2 | | X³+3x-10=0 | | -6(w+5)+8=-58 | | 2y=5y/6+4 | | 4(2+3x)+18=2× | | 5d–d–2d+8-3d=0 | | 5x+8=3-10 | | 5/17x-4x=-2x+20/21 | | 14+3n=8n-3{n-4} | | 3e+5=7 | | 9(y-4)-7y=6(3y-2) | | 3x-8=4(-3-8/4x) | | y+(20y/100)=1200 | | 4x+3+2x=3x+27 | | w-10=4.6 | | 3^3-3x^2-6x=0 | | 7n-4=4n+8 | | -4z+7+z=22 | | 7/24(8/39a-1)=-87 | | 0.18(y-9)+0.02y=0.10y-2.1 | | 5-9a=58 | | 3x^2-12x-1=-1 | | -6-3n+7=9-2n | | 6(y)-8-6-8(y)=4 |